Age, growth, and reproductive biology of Achilles tang (Acanthurus achilles) around Hawai'i Island, USA - Timothy B. Grabowski; Richard Masse; Dawn McSwain; Annie Larson; Lillian J. Tuttle Raz; Eva Schemmel; Danielle E. Bartz; Nikola Rodriguez (Environmental Biology of Fishes, 2025)

Investigating Children as Gatekeepers to Tactical Athlete Nutrition - J. Joyce; A. Sampson; P. Gonzalez Sanchez; B. Tuttle (Journal of the Academy of Nutrition and Dietetics, 2024)

Investigation of Significant Others as Gatekeepers to Tactical Athlete Nutrition - J. Joyce; M. Green; P. Gonzalez Sanchez; B. Tuttle (Journal of the Academy of Nutrition and Dietetics, 2023)

Oiling of American white pelicans, common loons, and northern gannets in the winter following the Deepwater Horizon (MC252) oil spill - J. D. Paruk; I. J. Stenhouse; B. J. Sigel; E. M. Adams; W. A. Montevecchi; D. C. Evers; A. T. Gilbert; M. Duron; D. Long; J. Hemming; P. Tuttle (Environmental Monitoring and Assessment, 2019)
The Natural Resource Damage Assessment and Restoration Trustees for the Deepwater Horizon oil spill assessed the external oiling of migratory bird species dependent on open water in the Gulf of Mexico following the aforementioned spill. The assessment was designed to evaluate birds that use open water during the winter within 40 km of the Gulf shoreline. We focused on the American white pelican ( Pelecanus erythrorhynchos ), common loon ( Gavia immer ), and northern gannet ( Morus bassanus ). Point counts (pelican, loon) or strip transects (gannet) were used and each target species was assessed for oiling (unoiled, trace, light, moderate, or heavy amounts) and photographed. Due to distance at sighting and/or poor visibility, not all visible birds were assessed. The percentage of birds oiled varied by species, with the common loon being the highest (23.6%), followed by American white pelican (16.9%), and northern gannet (6.9%). Most of the American white pelicans and common loons had trace (83% and 72%, respectively) or light levels (11% and 24%, respectively) of oiling. The northern gannet had just trace levels of oiling. Some pelicans (6%) and loons (4%) had moderate amounts of oiling. Based on expert derived-mortality estimates and our estimates of oil exposure, we used Monte Carlo simulations to predict expected decreases of 2.5%, 4%, and 11% in the observed population for the northern gannet, American white pelican, and common loon, respectively. While these values are underestimates of the true values given the long time lag (10–12 months) between the oil spill and the assessment, these data represent some of the few estimates of exposure for these species and describe minimum risk estimates to these species.

Estimation of 3D Ground Reaction Force Using Nanocomposite Piezo-Responsive Foam Sensors During Walking - Parker G. Rosquist; Gavin Collins; A. Jake Merrell; Noelle J. Tuttle; James B. Tracy; Evan T. Bird; Matthew K. Seeley; David T. Fullwood; William F. Christensen; Anton E. Bowden (Annals of Biomedical Engineering, 2017)

Effects of bottom‐layer hypoxia on spatial distributions and community structure of mesozooplankton in a sub‐estuary of Puget Sound, Washington, U.S.A - Julie E. Keister; Loren B. Tuttle (Limnology and Oceanography, 2013)
We investigated the response of mesozooplankton to low dissolved oxygen (DO) concentrations in Hood Canal, Washington, a seasonally hypoxic sub‐estuary of Puget Sound. Depth‐stratified zooplankton net tows were conducted above and below the oxycline during day and night in midsummer (July), late summer (September), and early winter (December) 2008 using closing nets. Bottom DO concentrations declined slowly through summer. In July, DO at most stations was low but not hypoxic. By late summer, bottom waters throughout the study area were hypoxic (≤ 2 mg L −1 ) and were severely hypoxic ( −1 ) at some stations. In winter, water‐column mixing and lower surface primary production resulted in higher DO, although sub‐pycnocline hypoxia persisted through December at some locations. Zooplankton abundance decreased from midsummer to winter. The community was dominated by gelatinous zooplankton and copepods. A shift in community structure towards a higher dominance of polychaetes and the cyclopoid copepod Oithona similis occurred over the season. Temporal and spatial patterns in zooplankton communities were primarily structured by month and bottom depth. DO played a lesser role in structuring the species composition, but vertical distributions of several taxa changed in response to hypoxia, with a greater proportion of their populations found above the oxycline during both day and night where bottom oxygen was low. However, some taxa were abundant below the oxycline, even at oxygen levels −1 ; these taxa may have a high tolerance to hypoxia, use low‐oxygen regions as a predation refuge, and be useful indicators of poor water‐quality conditions.

Partial heat acclimation of athletes with spinal cord lesion - Paul C. Castle; B. Pasan Kularatne; John Brewer; Alexis R. Mauger; Ross A. Austen; James A. Tuttle; Nick Sculthorpe; Richard W. Mackenzie; Neil S. Maxwell; Anthony D. J. Webborn (European Journal of Applied Physiology, 2013)

Intranasal delivery of deferoxamine reduces spatial memory loss in APP/PS1 mice - Leah R. Hanson; Jared M. Fine; Dan B. Renner; Aleta L. Svitak; Rachel B. Burns; Thuhien M. Nguyen; Nathan J. Tuttle; Dianne L. Marti; S. Scott Panter; William H. Frey (Drug Delivery and Translational Research, 2012)

The Use of Ground-Penetrating Radar to Accurately Estimate Soil Depth in Rocky Forest Soils - Eric B. Sucre; John W. Tuttle; Thomas R. Fox (Forest Science, 2011)
Ground-penetrating radar (GPR) is a geophysical tool that has the capability, given favorable soil properties, to improve the accuracy of soil depth estimation, compared with other commonly used methods. This study was conducted on three different physiographic regions across the southern Appalachian Mountains: the Ridge and Valley (n = 9), Cumberland Plateau (n = 6), and Allegheny Plateau (n = 6). At each site (n = 21), a 20- × 20-m measurement plot was scanned using both 200- and 400-MHz antennas to estimate average soil depth. Soil depth estimates obtained from both GPR antennas were compared with each other as well as with soil depth estimations obtained with a soil auger using a paired t test (α = 0.05). No significant differences in soil depth were observed for the 200- versus 400-MHz antennas (P = 0.913). Consequently, data recorded from the 400-MHz antenna were used when depth measurements between the GPR and soil auger were compared. This was done because of the smaller and lighter antenna size and better practicality (i.e., can be used by a single operator) compared with the heavier and bulky 200-MHz antenna. Across all plots (n = 21), depth estimations were shallower using a soil auger compared with estimates obtained using GPR across all plots (P = 0.0002). Results from this study demonstrate how current methods can underestimate soil depth in rocky forest soils. Depth estimations from GPR could be used to more accurately quantify site quality in the southern Appalachians by providing the precise data needed to calculate nutrient availability and water-holding capacity. Last, the reduction in size and weight of GPR antennas and computers now provides forest scientists a practical and powerful technology that should be revisited because it has been confined to very specific applications over the last 25 years.

Spatial characterization of electrical power consumption patterns over India using temporal DMSP‐OLS night‐time satellite data - T. R. Kiran Chand; K. V. S. Badarinath; C. D. Elvidge; B. T. Tuttle (International Journal of Remote Sensing, 2009)

Active forest fire monitoring in Uttaranchal State, India using multi‐temporal DMSP‐OLS and MODIS data - T. R. Kiran Chand; K. V. S. Badarinath; M. S. R. Murthy; G. Rajshekhar; C. D. Elvidge; B. T. Tuttle (International Journal of Remote Sensing, 2007)

Mapping and Modeling the Biogeochemical Cycling of Turf Grasses in the United States - Cristina Milesi; Steven W. Running; Christopher D. Elvidge; John B. Dietz; Benjamin T. Tuttle; Ramakrishna R. Nemani (Environmental Management, 2005)

Satellite observation of Keppel Islands (Great Barrier Reef) 2002 coral bleaching using IKONOS data - Christopher D. Elvidge; John B. Dietz; Ray Berkelmans; Serge Andréfouët; William Skirving; Alan E. Strong; Benjamin T. Tuttle (Coral Reefs, 2004)

Satellite observation of Keppel Islands (Great Barrier Reef) 2002 coral bleaching using IKONOS data - Christopher D. Elvidge; John B. Dietz; Ray Berkelmans; Serge Andréfouët; William Skirving; Alan E. Strong; Benjamin T. Tuttle (Coral Reefs, 2004)

Methods of double-stranded RNA-mediated gene inactivation in Arabidopsis and their use to define an essential gene in methionine biosynthesis - Joshua Z. Levin; Annick J. de Framond; Ann Tuttle; Michael W. Bauer; Peter B. Heifetz (Plant Molecular Biology, 2000)

Calcium homeostasis and nerve growth factor secretion from vascular and bladder smooth muscle cells - Todd B. Sherer; David B. Clemow; Jeremy B. Tuttle (Cell and Tissue Research, 2000)

Effects of growth rate and cell density on nerve growth factor secretion in cultures of vascular and bladder smooth muscle cells from hypertensive and hyperactive rats - David B. Clemow; J. B. Tuttle (Cell and Tissue Research, 1998)

Thrombin regulates nerve growth factor secretion from vascular, but not bladder smooth muscle cells - T. B. Sherer; J. M. Spitsbergen; W. D. Steers; J. B. Tuttle (Cell and Tissue Research, 1997)